23.4k views
5 votes
Differentiate with respect to x and simplify your answer. Show all the appropriate steps? 1.e^-2xlog(ln x)^3 2.e^-2x(log(ln x))^3 3.sin(xe^x)^3 4.sin^3(xe^x) 5.ln(xy)=e^2y

Differentiate with respect to x and simplify your answer. Show all the appropriate-example-1

1 Answer

3 votes

(1) I assume "log" on its own refers to the base-10 logarithm.


\left(e^(-2x)\log(\ln x)^3\right)'=\left(e^(-2x)\right)'\log(\ln x)^3+e^(-2x)\left(\log(\ln x)^3\right)'


=-2e^(-2x)\log(\ln x)^3+(e^(-2x))/(\ln10(\ln x)^3)\left((\ln x)^3\right)'


=-2e^(-2x)\log(\ln x)^3+(3e^(-2x)(\ln x)^2)/(\ln10(\ln x)^3)\left(\ln x\right)'


=-2e^(-2x)\log(\ln x)^3+(3e^(-2x)(\ln x)^2)/(\ln10\,x(\ln x)^3)


=-2e^(-2x)\log(\ln x)^3+(3e^(-2x))/(\ln10\,x\ln x)

Note that writing
\log(\ln x)^3=3\log(\ln x) is one way to avoid using the power rule.

(2)


\left(e^(-2x)(\log(\ln x))^3\right)'=(e^(-2x))'(\log(\ln x))^3+e^(-2x)\left(\log(\ln x))^3\right)'


=-2e^(-2x)(\log(\ln x))^3+3e^(-2x)(\log(\ln x))^2(\log(\ln x))'


=-2e^(-2x)(\log(\ln x))^3+3e^(-2x)(\log(\ln x))^2((\ln x)')/(\ln10\,\ln x)


=-2e^(-2x)(\log(\ln x))^3+(3e^(-2x)(\log(\ln x))^2)/(\ln10\,x\ln x)

(3)


\left(\sin(xe^x)^3\right)'=\left(\sin(x^3e^(3x))\right)'=\cos(x^3e^(3x)(x^3e^(3x))'


=\cos(x^3e^(3x))((x^3)'e^(3x)+x^3(e^(3x))')


=\cos(x^3e^(3x))(3x^2e^(3x)+3x^3e^(3x))


=3x^2e^(3x)(1+x)\cos(x^3e^(3x))

(4)


\left(\sin^3(xe^x)\right)'=3\sin^2(xe^x)\left(\sin(xe^x)\right)'


=3\sin^2(xe^x)\cos(xe^x)(xe^x)'


=3\sin^2(xe^x)\cos(xe^x)(x'e^x+x(e^x)')


=3\sin^2(xe^x)\cos(xe^x)(e^x+xe^x)


=3e^x(1+x)\sin^2(xe^x)\cos(xe^x)

(5) Use implicit differentiation here.


(\ln(xy))'=(e^(2y))'


((xy)')/(xy)=2e^(2y)y'


(x'y+xy')/(xy)=2e^(2y)y'


y+xy'=2xye^(2y)y'


y=(2xye^(2y)-x)y'


y'=\frac y{2xye^(2y)-x}

User Reznor
by
4.9k points